Effect of fenofibrate on serum and tissue sialic acid levels in short-term experimental hypercholesterolemia - (:unkn) unknown (GEORG THIEME VERLAG KG, 2007)
In recent years, sialic acid is considered to be a possible marker for cardiovascular diseases. The aim of this study was to investigate the effect of two different treatment periods of fenofibrate (CAS 49562-28-9) on serum, heart and liver sialic acid levels in experimental hypercholesterolemia. Serum, heart and liver total sialic acid levels were determined by Warrens thiobarbituric acid (TBA) method and serum lipid levels by commercial kits at the end of the fenofibrate treatment for 3 and 6 weeks. Fenofibrate treatment reduced serum total sialic acid levels significantly in the control and hypercholesterolemic groups at the end of the 3(rd) week and only in the control group at the end of the 6(th) week. Serum sialic acid levels of fenofibrate-treated hypercholesterolemic rats in the 6-week period were significantly higher than those in the 3-week period. Neither the hypercholesterolemic diet nor fenofibrate had any significant effect on heart and liver sialic acid levels. In conclusion, decreased serum sialic acid levels in control and hypercholesterolemic groups by fenofibrate short-term treatment may contribute to the decreased risk of cardiovascular diseases that accompanies the hypercholesterolemic complications. The decreased serum sialic acid levels further indicate the clinical efficacy of fenofibrate as an anti-inflammatory agent.
Keywords: CAS 49562-28-9; fenofibrate, effect on sialic acid levels; hypercholesterolemia, experimental; hypolipidemic drugs; sialic acid, in heart and liver; N-ACETYLNEURAMINIC ACID; C-REACTIVE PROTEIN; GENE-EXPRESSION; HEPATIC-FIBROSIS; VITAMIN-E; IN-VIVO; RAT; DECREASES; OLIGOSACCHARIDES; CHOLESTEROL